2002
DOI: 10.1359/jbmr.2002.17.5.774
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cyclo-Oxygenase-2 in Osteoclast Formation and Bone Destruction in Bone Metastasis of Mammary Carcinoma Cell Lines

Abstract: We previously reported that mouse mammary carcinoma cell lines (MMT060562 and BALB/c-MC) induced osteoclast formation through production of prostaglandin E 2 (PGE 2 ) in cocultures with mouse bone marrow cells, but the mechanism(s) of PG production remained unclear. In the present in vitro and in vivo studies, we tested the involvement of cyclo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 32 publications
(44 reference statements)
2
48
2
Order By: Relevance
“…We observed that PTH induction of c-Fos, Pghs2 and Il6, genes involved in osteoclast formation and signaling (33)(34)(35)(36)(37), was slightly decreased in KO compared to WT cultures (data not shown). Thus, these preliminary observations suggest that CREM deficiency may affect the nature of the intermittent PTH response by modulating genes involved in osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…We observed that PTH induction of c-Fos, Pghs2 and Il6, genes involved in osteoclast formation and signaling (33)(34)(35)(36)(37), was slightly decreased in KO compared to WT cultures (data not shown). Thus, these preliminary observations suggest that CREM deficiency may affect the nature of the intermittent PTH response by modulating genes involved in osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 93%
“…Invasive breast cancers, which constitutively express inducible Cox-2, enhance osteoclast formation through the production of high levels of PGE2 and subsequently an increase of osteolysis (Ono et al, 2002). As an important mechanism involved in the effect of BPs in bone marrow metastasis is the reduction of osteoclast-induced bone osteolysis, we also analysed whether ZOL could inhibit osteoclast activation by cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism that contributes to osteoclast activation and metastasis-induced osteolysis is the release of PGE2 by cancer cells (Ono et al, 2002). Therefore, we evaluated the action of ZOL on Cox-2 mRNA and protein expression in MDA-MB-231 cells.…”
Section: Inhibition Of Cox-2 Expression and Pge2 Release By Zol On MDmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is a potent stimulator of osteoclast formation and can enhance the effects of PTHrP on osteoclasts [19,20]. Breast cancer cells also produce IL-1, TNF and prostaglandins which increase RANKL expression and stimulate osteoclasts [21,22]. A recent study showed that breast cancer cells could stimulate survival of osteoclastogenesis and prolong osteoclast survival by expressing and secreting CSF-1 [23,24].…”
Section: Osteolytic Metastasismentioning
confidence: 99%